Th9 cells in inflammatory bowel diseases - Weigmann, Benno; Neurath, Markus (Seminars in Immunopathology, 2017)
Inflammatory bowel diseases are chronic, relapsing, immunologically mediated disorders of the gastrointestinal tract. Emerging evidence suggests a critical functional role of transcription factors and T cell-related cytokines in ulcerative colitis and Crohn's disease. Gut-residing T cells from patients with inflammatory bowel disease produce high amounts of IL-9. Experimental models of colitis highlighted that IL-9-producing T cells critically interfered with an intact barrier function of the intestinal epithelium by impacting cellular proliferation and tight junction molecules. The blockade of IL-9 was suited to significantly ameliorate the disease activity and severity in experimental models of inflammatory bowel disease thereby suggesting that targeting IL-9 might function as a novel targeted approach for therapy.
EVALuna2:33831